Fluvial waters toxicology related to its land use and land cover - Gavlak, Guilherme (2024)
Due to uncontrolled population growth and intensified anthropic activities, numerous environmental impacts occur in water bodies, such as the toxicity of their waters. This study aimed to evaluate the water toxicity of the Antas River through ecotoxicological bioassays using neonates of the microcrustacean Daphnia magna, and to relate it to land use and land cover in areas near the river. Fourteen sampling points were selected along the entire assessed stretch of the river, and water samples were collected and subjected to acute toxicity analyses using neonates. Land use and land cover mapping of the Antas River Watershed was generated, and an analysis was conducted within approximately a 400-meter radius from each sampling point. The occupation rates for each evaluated area were quantified and subsequently correlated with the obtained toxicity data. The results revealed a high significance level (99%) indicating that land use and land cover in the vicinity of water bodies directly influence water toxicity, impacting it in urban areas or preserving it in native forest areas, depending on the land use, as assessed through acute assays using neonates of the microcrustacean Daphnia magna.